Insights Into Cigarette Litigation From a Career Tobacco Dependence Physician: The Florida Engle Trials - Richard D. Hurt (Journal of Primary Care & Community Health)
The purpose of this commentary is to better inform physicians about the often-unrecognized consequences of cigarette smoking. It highlights knowledge gained from involvement in over 70 legal cases between smokers and cigarette companies in the Florida Engle Trials. As a physician with many years of experience in treating nicotine addiction, the author participated as a paid expert witness in these cases, 45 of which went to trial. Depositions included family members and close associates of the smoker, which allowed the gathering of voluminous information not usually available to a physician. This provided a level of insight into the suffering experienced that was illuminating. Based on this experience as an expert witness, 3 cases are presented that are clear examples of the tragedy experienced by smokers and their families. While not randomly selected, they are representative of the cases in which I participated. The impact of cigarettes on both smokers and those around them is difficult to quantify and is often not observable by healthcare professionals. The documented attitudes of cigarette lawyers, as seen in depositions and at trials, demonstrate an incredible lack of empathy and compassion. On the other hand, the cigarette companies are completely aware that almost 500 000 Americans die each year from use of their products, but death is only 1 outcome. What a sad commentary on the companies that knowingly perpetuated this epidemic and the lawyers who continue to defend them. Sadly, to both parties, it isn’t about the pain, suffering, morbidity, and death that these products cause. Rather, it is simply about money and staying in business on the one hand and money and winning on the other. However, the paramount lesson learned for all of us who take care of smoking patients is first to help them stop smoking and second to appreciate the wide-reaching ramifications of their tobacco dependence. Taking this empathic approach to their care will go a long way to demonstrating the compassion that is needed to provide a healing environment for the patient, their family, and loved ones.